Social dominance in rats is a determinant of susceptibility to stress - Durga J. Srinivasan; Vijayakumar Kapgal; Richard G. M. Morris; Sumantra Chattarji (Proceedings of the National Academy of Sciences, 2025)
Establishing a dominance hierarchy in social organisms is important for access to resources. Stress has been proposed as a major factor influencing an animal’s likely position in a social hierarchy. Although individual differences in vulnerability to stress are increasingly recognized, how social hierarchy affects vulnerability remains relatively understudied. Here, we examined how the social dominance status of adult male Sprague-Dawley rats influences their response to stress in interactions with a familiar animal living in the same cage, and separately when confronting an unfamiliar rat of uncertain dominance status from another cage, using the tube test. Having determined the relatively stable within-cage social dominance status of animals, half were subjected to a single episode of 2-h immobilization stress. Cagemates, both control and stressed rats, again faced one another 1 d and 10 d after stress. First, the predetermined hierarchical rank among familiar cagemates was relatively unaffected by stress. However, second, the same stress had a differential impact in competitions between unfamiliar rats. Socially dominant control rats continued to win competitions but subordinate control rats, that had previously lost, sometimes started to win against previously dominant rats that had been stressed. Strikingly, subordinate stressed rats displayed consistent submissive-like behavior and they alone showed differential effects on dendritic spine density in the amygdala. Thus, an individual’s social rank can influence its response to stress, an effect that is detectable in interactions with unfamiliar animals. These findings provide an additional dimension to animal models of stress used for exploring facets of social anxiety and withdrawal in stress-related psychiatric disorders.